Does Self-Determination Theory help explain the impact of social prescribing? A qualitative analysis of patients' experiences of the Glasgow 'Deep-End' Community Links Worker Intervention. (September 2021) - Hanlon, Peter; Gray, Cindy M; Chng, Nai Rui; Mercer, Stewart W
Objectives: The Links Worker Programme is a primary care-based social prescribing initiative in Glasgow, Scotland, targeting patients with complex needs in areas of high socioeconomic deprivation. The programme aims to improve wellbeing by connecting patients to appropriate community resources. This study explored the utility of Self-Determination Theory in understanding the reported impacts of the intervention. Methods: Thematic analysis of semi-structured interviews with 12 patients (34–64 years, six female) referred to Community Links Practitioners using Self-Determination Theory as a framework. Impact was assessed from participants' description of their personal circumstances before and after interaction with the Community Links Practitioner. Results: Four patients described no overall change in daily life, two described slight improvement and six described moderate or major improvement. Improvers described satisfaction of the three psychological needs identified in Self-Determination Theory: relatedness, competence and autonomy. This often related to greater participation in community activities and sense of competence in social interaction. Patients who benefitted most described a change towards more intrinsic regulation of behaviour following the intervention. Conclusions: Understanding the impact of this social prescribing initiative was facilitated by analysis using Self-Determination Theory. Self-Determination Theory may therefore be a useful theoretical framework for the development and evaluation of new interventions in this setting.